2017
DOI: 10.1038/eye.2017.228
|View full text |Cite
|
Sign up to set email alerts
|

Early deep anterior lamellar keratoplasty for fungal keratitis poorly responsive to medical treatment

Abstract: PurposeTo investigate the efficacy of early therapeutic deep anterior lamellar keratoplasty (DALK) in eradicating fungal keratitis that is poorly responsive to medical treatment.Patients and methodsTwenty-three eyes (23 patients) underwent early therapeutic DALK within 15 to 50 days from the onset of symptoms. The adopted eligibility criteria for early DALK included the following: active fungal keratitis affecting the optical zone with ulcer confined in the 6.00 mm central cornea; deeper than 150 μm but not ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…As they are often young and otherwise healthy, their corneal endothelium is of far better quality than one can expect after penetrating keratoplasty (PK). Therefore, preserving the endothelium with the Descemet membrane, with total resection of the infiltrate was tried in several studies [37,38,39,40,41]. In all of them, DALK was considered as a viable alternative for PK, with considerable advantages of lower immune rejection and graft dehiscence, but limited by the depth of the fungal infiltrate -i.e.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…As they are often young and otherwise healthy, their corneal endothelium is of far better quality than one can expect after penetrating keratoplasty (PK). Therefore, preserving the endothelium with the Descemet membrane, with total resection of the infiltrate was tried in several studies [37,38,39,40,41]. In all of them, DALK was considered as a viable alternative for PK, with considerable advantages of lower immune rejection and graft dehiscence, but limited by the depth of the fungal infiltrate -i.e.…”
Section: Case Reportmentioning
confidence: 99%
“…In all of them, DALK was considered as a viable alternative for PK, with considerable advantages of lower immune rejection and graft dehiscence, but limited by the depth of the fungal infiltrate -i.e. Sabatino et al did not consider it in ulcers deeper than 300mm [39]. The biggest disadvantage of this approach is the difficult surgical technique, and risk of leaving some fungal hyphae unnoticed in the deeper layers of the cornea, but this can be minimized with careful patient selection.…”
Section: Case Reportmentioning
confidence: 99%
“…Once fungi reach the deep stroma, they can penetrate into the anterior chamber and there is a high risk of endophthalmitis that can lead to ocular enucleation. One study suggested early deep anterior lamellar keratoplasty as a possible safe therapeutic approach to effectively eradicate fungal keratitis affecting the optic zone and poorly responsive to medical treatment, thus avoiding corneal transplant [ 12 ]. Therapeutic options against these fungi are limited by low tissue penetration in the eye due to ocular barriers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although DALK has numerous benefits and its indications are increasingly expanding (keratoconus, stromal dystrophies, scars, and, recently, even active infections poorly responsive to medical treatment), the technique is commonly considered challenging. [4][5][6][7][8][9][10] Descemet's membrane (DM) rupture is the most common (4%-39% of cases) and feared intraoperative complication, accounting for the leading cause of PK conversion. 1,3,11,12 Although different strategies have been described to repair DM ruptures, this complication can be difficult to manage.…”
Section: Introductionmentioning
confidence: 99%